Have coffee producers benefited from the new domestic cherry market?: Evidence using panel data from Rwanda - Murekezi, Abdoul; Jin, Songqing; Loveridge, Scott (Wiley, 2014)
The article assesses the effects of the new domestic cherry market on coffee‐growing households in Rwanda using panel data. Findings from combined first differenced with instrumental variable specification and other estimation methods provide evidence that farmers who sell to the cherry market do not increase their expenditures compared to farmers selling to the traditional parchment market. The different time lags in terms of when farmers started selling to the new cherry market may explain the lack of statistically significant differences across the two groups. It is possible that farmers will adjust their expenditure patterns in subsequent periods after year‐over‐year market trends become more apparent to them.